Who’s afraid of Local Agenda 21? Top-down and bottom-up perspectives on local sustainability - Schmidt, Luísa (2016)
Local Agenda 21 is essentially a process of democratic practicing, insofar as it involves sharing political competencies in decision making by the local authorities, and the mobilisation of all citizens and civil society organisations in the process. It is, thus, a course of action in which the willingness and openness of local political leaders is as important as the ability of citizens to take the initiative of learning about and getting involved in local public life. Unfortunately, there are no more than twenty LA21 processes running in Portugal, and most of them do not fulfil all the parameters required. This paper discusses some hypotheses on the lack of success of LA21 in Portugal, which are related to structural political conditions for local governance and public participation. Resorting to some surveys on environmental policy issues (applied to both the municipal leaders and the population), the aim is to characterise the trends of mobilisation on local sustainability in Portuguese society, particularly with regard to the citizenry and local administrations.